Heat tolerance studies for wheat improvement - Talukder, Shyamal Krishna (Kansas State University, 2014)
Heat stress is one of the major environmental constraints for wheat production worldwide. High temperature during grain filling in wheat leads to a significant reduction in yield. In this research, three different projects were completed. The first project was to study cytoplasmic effects on heat tolerance in wheat, where ten different alloplasmic lines of wheat were backcrossed with four different wheat varieties: „Karl 92‟, „Ventnor‟, „U1275‟ and „Jagger‟. The nuclear genome of the alloplasmic lines was substituted by backcrossing six times using the recurrent parents as males. During the fifth and/or fourth backcross, reciprocal crosses were made to develop NILs (Near Isogenic Lines) for cytoplasm. Sixty-eight NILs and their parents were evaluated in growth chambers for post-anthesis heat tolerance. Plants were grown in the greenhouse and placed under heat stress for 14 days starting at 10 days after anthesis. Growth chambers were maintained at 35°/30°C for heat stress and the greenhouse was maintained at 20°/15°C as the optimum temperature. Effects of high temperature on chlorophyll content and Fv/Fm (a chlorophyll fluorescence measuring parameter) were found to be significant. Cytoplasms 1, 4, 5, 8, 9 and10 provided greater tolerance in one or more nuclear backgrounds. These results indicated that cytoplasmic effects can contribute to heat tolerance of wheat. The second project focused on identification of quantitative trait loci (QTL) for thylakoid membrane damage (TMD), SPAD chlorophyll content (SCC) and plasma membrane damage (PMD), as these traits are found to be associated with resistance to heat stress and contributes to relatively stable yield under high temperature. A RIL (Recombinant Inbred line) population of a cross between winter wheat cultivars „Ventnor‟ and „Karl 92‟ was evaluated using two different temperature regimes (20°/15°C, 36°/30°C) imposed at ten days after anthesis. The aforementioned traits were evaluated and associated with various molecular markers (SSR, AFLP and SNP). The putative QTL associated are localized on chromosomes 6A, 7A, 1B, 2B and 1D and have the potential to be used in marker assisted selection for improving heat tolerance in wheat. In the third project, a transgenic approach to increase grain fill during high temperatures was investigated. Grain fill is reduced at temperatures above 25°C in wheat partly due to the inactivity of soluble starch synthase. We isolated a soluble starch synthase gene from rice that has the potential to overcome this deficiency during high temperatures and placed it behind both a constitutive promoter and an endosperm-specific promoter. Transgene expression and the effects of the transgene expression on grain yield-related traits for four generations (T0, T1, T2 and T3) were monitored. The results demonstrated that even after four generations, the transgene was still expressed at high levels, and transgenic plants produced grains of greater seed weight than Bobwhite control plants under the same environmental conditions. Thousand-seed weight under high temperatures increased 21-34% in T2 and T3 transgenic plants when compared to the non-transgenic control plants. In addition, the duration of photosynthesis was longer in transgenic wheat than in non-transgenic controls. Our study demonstrated that expression of rice soluble starch synthase gene in wheat can improve wheat yield under heat stress conditions.
Keywords: Alloplasmic line; QTL mapping; Starch synthase; Heat tolerance; Agronomy (0285); Plant Sciences (0479)